Lactoferrin Disaggregates Pneumococcal Biofilms and Inhibits Acquisition of Resistance Through Its DNase Activity - Angulo-Zamudio, Uriel A.; Vidal, Jorge E.; Nazmi, Kamran; Bolscher, Jan G. M.; Leon-Sicairos, Claudia; Antezana, Brenda S.; Canizalez-Roman, Adrián; León-Sicairos, Nidia (Frontiers in Microbiology, 2019)
Streptococcus pneumoniae colonizes the upper airways of children and the elderly. Colonization progresses to persistent carriage when S. pneumoniae forms biofilms, a feature required for the development of pneumococcal disease. Nasopharyngeal biofilms are structured with a matrix that includes extracellular DNA (eDNA), which is sourced from the same pneumococci and other bacteria. This eDNA also allows pneumococci to acquire new traits, including antibiotic resistance genes. In this study, we investigated the efficacy of lactoferrin (LF), at physiological concentrations found in secretions with bactericidal activity [i.e., colostrum (100 µM), saliva (25 µM)], in eradicating pneumococcal biofilms from human respiratory cells. The efficacy of synthetic LF-derived peptides was also assessed. We first demonstrated that LF inhibited colonization of S. pneumoniae on human respiratory cells without affecting the viability of planktonic bacteria. LF-derived peptides were, however, bactericidal for planktonic pneumococci but they did not affect viability of pre-formed biofilms. In contrast, LF (40 and 80 µM) eradicated pneumococcal biofilms that had been pre-formed on abiotic surfaces (.i.e., polystyrene) and on human pharyngeal cells, as investigated by viable counts and confocal microscopy. LF also eradicated biofilms formed by S. pneumoniae strains with resistance to multiple antibiotics. We investigated whether treatment with LF would affect the biofilm structure by analyzing eDNA. Surprisingly, in pneumococcal biofilms treated with LF, the eDNA was absent in comparison to the untreated control (10µg/ml) or those treated with LF-derived peptides. EMSA assays showed that LF binds S. pneumoniae DNA and a time-course study of DNA decay demonstrated that the DNA is degraded when bound by LF. This LF-associated DNase activity inhibited acquisition of antibiotic resistance genes in both in vitro transformation assays and in a life-like bioreactor system. In conclusion, we demonstrated that LF eradicates pneumococcal-colonizing biofilms at a concentration safe for humans and identified a LF-associated DNAse activity that inhibited the acquisition of resistance.